Evolution of the consumption trend of proton pump inhibitors in the Lleida Health Region between 2002 and 2015 - Torres-Bondia, F.; de Batlle, J.; Galván, L.; Buti, M.; Barbé, F.; Piñol-Ripoll, G. (BMC public health, 2022)
Background Proton pump inhibitors (PPIs) are one of the most commonly prescribed pharmacological groups. Their high prevalence and duration of use are of important health concern due to the risk they can cause to patients. Despite these risks, their use remains particularly high, especially in the elderly population. We determined the trend in the prevalence of PPI consumption in the population of the Lleida Health Region between 2002 and 2015 to explore patterns of use and associated characteristics. Methods An analysis of secular trends between 2002 and 2015 was performed. The database included all individuals who used PPIs in the Lleida Health Region, which had 358.070 inhabitants in 2015. PPI use was evaluated using prescription dispensing data from the public health system. All types of PPIs approved by the pharmaceutical agency were included. Trends were investigated by age and sex. Results For the whole study period, a total of 215,417 individuals accounted for 292,122 dispensations. Overall, 48% were women, and the mean age was 62 years. The dispensing prevalence of PPI use in 2015 was 18.0% overall—20.4% for women and 15.7% for men—and was 54.6% for those over 65 years. In terms of the subtypes of PPIs, 16.8% of prescriptions were for omeprazole, 0.66% were for pantoprazole, and 0.48% were for lansoprazole. The evolution of the annual PPIs dispensation prevalence showed a progressive increase from 11.3% in 2002 to 18.0% in 2015, which was attributable to an increase in the use of omeprazole (9.0% vs. 16.8%) and, to a lesser extent, esomeprazole (0.02% vs. 0.4%). Conclusion An increase in the prevalence of PPI dispensation was observed over 14 years of follow-up. The prevalence of dispensation was especially high for the population older than 65 years, despite the risk of cognitive decline and falls. Comprehensive actions are required to to increase rational prescribing of PPIs, especially in high-risk populations.